TEXTUAL ARCHIVES MAINTENANCE MODEL AT THE OFFICE OF THE BARRU REGENCY OF LIBRARY AND CIVILITY - Usamah Mahmud (Jurnal Scientia, 2022)
This study aims to determine: the model of textual archive maintenance at the library and archives office of Barru Regency. And to find out the role of textual archives at the library and archives office of Barru Regency. Sources of data obtained by means of interviews and observations. Data Analysis Using Data Reduction, Data Presentation, Drawing Conclusions and Verification. The results of this study indicate the maintenance model for textual archives at the library and archives office of Barru Regency seen from the aspect of the maintenance model for textual archives is very good. the archivist provides a maintenance model, namely a camperization archive maintenance model, archive maintenance which is carried out by cleaning the archive first, followed by cleaning the archive box and roll o'pack by ending with sufficient camphor or camphor and treatment is carried out once a week.